PENGARUH KUALITAS DAUN MURBEI Morus multicaulis TERHADAP INDEKS NUTRISI ULAT SUTERA Bombyx mori L. (LEPIDOPTERA:BOMBICIDAE) - Maya Murni Chanigo; Masitta Tanjung; Nursal . (Saintia Biologi, 2013)
The effect of mulberry leaf quality on the nutrition index of silk worm was studied. The aim is to determine the effect mulberry leaf (Morus multicaulis) on the nutrition index of silkworm. The experiment used completely randomized design (CRD) with 2 treatments. The first treatment the leaves were taken from Morus multicaulis that cultivated in soil with NPK, Urea and TSP fertilizer. The second the plant were not fertilized at all. Nutrition index of silk worm was observed from instar III to instar V. Each treatment used 20 larvae. The result showed that leaf taken from a fertilized plant has significant nutrition index (p<0,05) on ECD (Efficiency Conversion of Digested Food), ECI (Efficiency Conversion of Ingested Food) in instar IV and V, and AD (Approximate Digesstibility) in instar III, IV and V. However, the GR (Growth Rate) and CR (Consumptio Rate) in instar III, IV and V showed no significant effect (p>0,05). Fertilizer only improves ECD (Efficiency Conversion of Digested Food) in instar IV with 45.45%. ECI (Efficiency Conversion of Ingested Food) with III and IV 15.42% : 30.76%, and the value of AD in instar III, IV and V are 11.49%, 12.16% and 8.38% respectively. Keywords: Morus multicaulis, Bombyx mori L., fertilizer, nutrition index